Interface pH regulation to improve ORR performance of FePc catalyst in acid electrolyte - Li, Yu-Yang; Wang, Yu-Cheng; Zhou, Zhi-You; Sun, Shi-Gang (Electrochemistry communications, 2022)
[Display omitted] •ORR performance of FePc is greatly improved by anion-exchange ionomer in acidic medium.•Anion-exchange ionomer can increase local pH of electrode/electrolyte interface.•The increase in interface pH was verified by in situ Raman technology. Iron–nitrogen doped carbon (Fe/N/C) electrocatalysts are among the most promising materials to replace Pt for the oxygen reduction reaction (ORR). Up to now, most work has been devoted to improving the performance of Fe/N/C catalysts by material design, while ignoring the design of the electrode/electrolyte interface environment. Considering the superior ORR performance of Fe/N/C catalysts in alkaline electrolyte, we attempt to construct a proton-deficient environment at the electrode surface to raise the local pH value. An anion-exchange ionomer with H+ blocking ability was chosen as the binder of the iron phthalocyanine (FePc) catalyst, a model molecule for Fe/N/C. The anion-exchange ionomer can increase the interface pH value as compared with commonly used Nafion binder, which was verified by the electrochemical shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) technique with CO32–/HCO3– as a probe. This strategy significantly improves the ORR activity and stability of the FePc catalyst in acidic medium.